2010
DOI: 10.1002/mrd.21179
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression analysis of Fshr and Lhr in relation to Fshb and Lhb subunits during the period of temperature‐dependent sex determination in pejerrey Odontesthes bonariensis

Abstract: In this study, we cloned and characterized the follicle stimulating hormone receptor (Fshr) and luteinizing hormone receptor (Lhr) cDNAs of pejerrey Odontesthes bonariensis, a species with temperature-dependent sex determination (TSD), and analyzed their expression in relation to Fshb and Lhb subunits during gonadogenesis at temperatures producing only females (17 degrees C, FPT), both sexes (25 degrees C, MixPT), and only males (29 degrees C, MPT). The pejerrey Fshr cDNA had 3,069 bp for a mature protein of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…fshr is expressed in the theca and granulosa cells of the ovary, and sertoli cells in the testis. It belongs to the G-protein-coupled membrane receptors superfamily and regulate gametogenesis and production of sexual steroids in teleost gonads (Shinoda et al, 2010). The neuroactive ligand-receptor interaction pathway was also enriched in Gymnocypris przewalskii brain under high temperature, where neuroactive ligand-receptor genes exhibited sex- and tissue-specific expression patterns (Tian et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…fshr is expressed in the theca and granulosa cells of the ovary, and sertoli cells in the testis. It belongs to the G-protein-coupled membrane receptors superfamily and regulate gametogenesis and production of sexual steroids in teleost gonads (Shinoda et al, 2010). The neuroactive ligand-receptor interaction pathway was also enriched in Gymnocypris przewalskii brain under high temperature, where neuroactive ligand-receptor genes exhibited sex- and tissue-specific expression patterns (Tian et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The relative expression levels were normalized using β‐ actin as internal control (forward: 5′‐CTCTGGTCGTACCACTGGTATCG‐3′; reverse: 5′‐ GCAGAGCGTAGCCTTCATAGATG‐3′; amplification size: 83 bp). The β‐ actin gene has already been used to normalize samples for DNA quantity in preview studies done in O. bonariensis larvae reared at different temperatures (Shinoda et al, ; Fernandino et al, ; Tovar Bohórquez et al, ). The heads of six larvae were randomly sampled every week for total RNA isolation using TRIzol Reagent (http://www.lifetechnologies.com) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, we found that the expression of GTHα in the brain reduced under high temperature in the induction and recovery groups. LHβ is another critical mediator of sexual development and its expression is modulated by cAMP/PKA system (Horton and Halvorson, 2004;Shinoda et al, 2010). Pérez et al (2011) found that low temperature caused a higher expression of LHβ and FSHβ in European eel pituitary and higher E2 levels.…”
Section: Tablementioning
confidence: 99%